Integrative mechanisms of plant salt tolerance: Biological pathways, phytohormonal regulation, and technological innovations - Abdul Waheed; Lu Zhuo; Minghui Wang; Xu Hailiang; Zewen Tong; Cuhan Wang; Aishajiang Aili (Plant Stress, 2024)
Salt stress is a major environmental challenge that profoundly impacts plant growth and development. The ability of plants to cope with high salinity involves with a complex network of biological mechanisms including osmoregulation, redox and ionic homeostasis, and hormones or light signaling-mediated growth adjustments. These adaptive responses are governed by various functional components that interact to modulate plant stress tolerance. This review provides a comprehensive overview of the current understanding of these mechanisms, focusing on the intricate regulatory networks that underpin plant salt tolerance. We explore the processes involved in the perception of salt stress, where plants detect changes in osmotic and ionic conditions, and the subsequent signaling pathways that activate stress responses. Key phytohormones such as abscisic acid (ABA), ethylene (ET), and brassinosteroids (BRs) play pivotal roles in these processes by regulating gene expression and coordinating adaptive growth responses. Additionally, this review explores physiological mechanisms like ion homeostasis, compatible solute synthesis, and antioxidant defense, alongside the role of root microbiota in enhancing nutrient uptake and stress mitigation under salinity. Emerging nanobiotechnologies, including nano-fertilizers and stress-sensing technologies, are highlighted for their role in improving plant resilience. By integrating molecular biology, plant physiology, and advanced technologies, the review emphasizes the multidisciplinary strategies needed to develop salt-tolerant cultivars and optimize agricultural practices in saline environments.